Eco-Enzyme Training: Biodegradable Waste Management - jannah, syayyidah; Fitri Rahajeng, Dinik; Sutyiono, Bayu (FEBI UIN Sunan Kalijaga Yogyakarta, 2022)
The increasing amount of trash that is increasing and complex can cause many problems. Waste disposal sites are sometimes unreliable for their carrying capacity, so educating the public about the importance of waste management and processing is an urgency. One method of managing and processing waste that can be done is to make an eco-enzyme solution. Eco-enzyme solution is made by utilizing waste from fruit and vegetable peels. Eco-enzyme solutions also have many household uses. Eco-enzyme training is important as a form of optimism for the community to care more about the environment.